2016
DOI: 10.1186/s12936-016-1296-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences in PfEMP1s recognized by antibodies from patients with uncomplicated or severe malaria

Abstract: BackgroundPlasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) variants are encoded by var genes and mediate pathogenic cytoadhesion and antigenic variation in malaria. PfEMP1s can be broadly divided into three principal groups (A, B and C) and they contain conserved arrangements of functional domains called domain cassettes. Despite their tremendous diversity there is compelling evidence that a restricted subset of PfEMP1s is expressed in severe disease. In this study antibodies from patients with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
2
20
1
Order By: Relevance
“…yoelli were detected in semi-immune than naive mice. This was consistent with our observation that the circulating parasites were older in the uncomplicated than the severe malaria patients because we previously showed that the uncomplicated malaria patients had more immunity to PfEMP1 than the severe malaria patients [ 88 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…yoelli were detected in semi-immune than naive mice. This was consistent with our observation that the circulating parasites were older in the uncomplicated than the severe malaria patients because we previously showed that the uncomplicated malaria patients had more immunity to PfEMP1 than the severe malaria patients [ 88 ].…”
Section: Discussionsupporting
confidence: 92%
“…A transcript incorporating DC5 (DBLÎŽ5-CIDRÎČ3-DBLÎČ7-[DBLÎł4]) (contig12688) was also up-regulated in severe malaria ( p = 0.0537). DC5 was up-regulated in severe malaria in Africa [ 48 ] and expressed in a cerebral malaria case in Papua New Guinea [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding B‐cells, a number of observations clearly demonstrate that B‐cell homeostasis is affected by Plasmodium infection . This can be attributed to the complex biology of the parasites , their antigenic diversity , and their immune‐modulatory molecules . The BAFF/APRIL system plays a variety of roles in immunomodulation, mainly by affecting B cell activation, proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium infection [17,18,44,45]. This can be attributed to the complex biology of the parasites [46,47], their antigenic diversity [46][47][48], and their immune-modulatory molecules [49,50]. The BAFF/APRIL system plays a variety of roles in immunomodulation, mainly by affecting B cell activation, proliferation, and survival.…”
Section: Malaria Is Characterized By Many Pathophysiological Changes mentioning
confidence: 99%
“…Immunity to severe malaria is generally acquired after only one to two severe episodes (24) with naturally acquired antibodies specific for PfEMP1 variants likely playing an important role in clinical protection (25). Antibodies to group A PfEMP1 variants tend to be acquired prior to antibodies to group B and C variants (26) and are associated with protection from severe malaria (27). Similarly, antibodies to EPCR-binding CIDRα1 domains are acquired more rapidly than antibodies to other CIDR domains in areas of high malaria transmission intensity and are boosted by severe malaria but not uncomplicated malaria (28, 29).…”
Section: Introductionmentioning
confidence: 99%